Paris-Rome-Madrid : l’influence de l’art français et romain sur les sculpteurs espagnols dans la première moitié du xixe siècle - Christiane Dotal (Mélanges de la Casa de Velázquez, 2006)
Paris-Rome-Madrid make up a unit constituting one aspect of the many artistic changes that took place in the Eternal City in the 19th century. Despite the desire of the Real Academia de San Fernando to encourage the training of Spanish artists in Paris and Rome, there was also considerable resistance, fuelled by an access of identity-affirmation. Spanish sculptors by themselves brought forth the traumatic events of the Peninsular War in their creations. However, the Antiquity they encountered in Rome, in which they had been initiated by Mengs in the late 18th century, remained their absolute model.